Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy111
|View full text |Cite
|
Sign up to set email alerts
|

I‐Self and Me‐Self Processes Affecting Developmental Psychopathology and Mental Health

Abstract: This chapter focuses on selected developmental psychopathologies during three stages of childhood and three stages of adolescence that involve the self . A new framework casts the Jamesian processes of the I‐self and the me‐self on center stage, as key actors in a conspiracy that is implicated in five forms of developmental psychopathology: (1) narcissism; (2) low self‐esteem; (3) depression and suicidal behaviors; (4) eating disorders; and (5) school violent revenge committed by humili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 187 publications
0
5
0
Order By: Relevance
“…Emotionally abused victims may adopt a negative self-image [129] and believe that they are not worthy of parental attention [130] due to the introjection of parents' harmful behavior such as criticism and insults [131]. Adverse childhood experiences can lead to maladaptive behaviors (e.g., suicidal ideation and related behaviors) through impairment of the self-concept ( [132], p. 470). Research suggests that maltreated children and youth have lower self-esteem and are more likely to engage in a range of risky behaviors, including substance abuse [133].…”
Section: Psychological Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Emotionally abused victims may adopt a negative self-image [129] and believe that they are not worthy of parental attention [130] due to the introjection of parents' harmful behavior such as criticism and insults [131]. Adverse childhood experiences can lead to maladaptive behaviors (e.g., suicidal ideation and related behaviors) through impairment of the self-concept ( [132], p. 470). Research suggests that maltreated children and youth have lower self-esteem and are more likely to engage in a range of risky behaviors, including substance abuse [133].…”
Section: Psychological Abusementioning
confidence: 99%
“…Such experiences can also increase attachment insecurity, avoidance, and isolation, which also play a significant role in the development of depression [104]. As already mentioned, consistent emotional abuse takes its toll, leading to a breakdown in the ability to effectively resist or cope with these experiences ( [132], p. 448). This is when individuals are more likely to become depressed; unable to escape anger, fear, shame, and guilt, they may attempt to cope by inhibiting all of these emotions.…”
Section: Psychological Abusementioning
confidence: 99%
“…childhood maltreatment) can lead to low self-esteem. 32 Some theorists have pointed out that large amounts of negative events would lead to learned helplessness, which might lead to low self-esteem. 33 Additionally, abundant empirical studies have found a positive association between childhood maltreatment and low self-esteem.…”
Section: Childhood Maltreatment and Self-esteem And Envymentioning
confidence: 99%
“…On the contrary, adverse childhood experiences (e.g. childhood maltreatment) can lead to low self‐esteem 32 . Some theorists have pointed out that large amounts of negative events would lead to learned helplessness, which might lead to low self‐esteem 33 .…”
Section: Relevant Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Researchers also focus on how SCD changes with age. Developmental psychologists regard self as a cognitive and social structure, which differentiates and integrates constantly with the development of cognitive abilities ( Labouvie-Vief et al, 1995 ; Harter, 2006 , 2016 ; Esnaola et al, 2018 ). Diehl et al (2001) described the age trajectory of SCD across the adult life span.…”
Section: Introductionmentioning
confidence: 99%